Training In Indonesian Language Skills And Realistic Mathematics To Improve Concept Understanding And Communication Among Primary School Pupils - Suharmono Kasiyun; Pance Mariati; Siti M. Amin; Syamsul Ghufron (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Abstract: This community service program was conducted at SDN Al Islah Surabaya to enhance teachers’ pedagogical competence through reading literacy strategies and the application of Realistic Mathematics Education (RME). A total of 20 elementary school teachers participated in a series of activities including needs assessment, workshops, interactive training, and classroom mentoring. Data collection involved observation, interviews, questionnaires, pre-tests, and post-tests. The results indicated significant improvements in teachers’ competencies, particularly in mastering reading comprehension strategies (SQ3R, reciprocal teaching, and graphic organizers), implementing RME in mathematics teaching, diversifying instructional methods, and facilitating student communication. Consequently, students showed notable progress in reading comprehension (62% to 81%), problem-solving in contextual math tasks (58 to 80), and active classroom participation (40% to 85%). In conclusion, literacy- and RME-based training, combined with interactive workshops and mentoring, proved effective in enhancing teachers’ pedagogical competence as well as students’ learning outcomes